Secretion from the Leishmania flagellum as a potential mechanism of virulence factor delivery - Makin, L (2017)
Protozoa of the Leishmania genus are transmitted between mammalian hosts by the sandfly and cause the neglected tropical disease leishmaniasis. Upon injection into the mammalian host by the sandfly promastigote-form parasites are phagocytosed by macrophages, where they differentiate into amastigotes. Although many virulence factors are known to modulate macrophage signalling pathways to favour infection, the delivery mechanisms are largely unknown. During differentiation to amastigotes the promastigote flagellum shortens dramatically and the fate of the excess flagellar membrane is unknown. Here we investigate the possibility that during Leishmania mexicana differentiation, shedding of the flagellar membrane is a source of extracellular vesicles (EVs) which provide a virulence factor delivery mechanism. The kinetics and structural mechanisms of EV release from promastigotes were investigated by live cell imaging and by measuring the concentration of shed EVs. Isolated EVs from a differentiating parasite culture or a control promastigote parasite culture were analysed by fluorescence and electron microscopy and mass spectrometry. To study the biological effects of EVs, macrophages were exposed to isolated EVs or live promastigotes and cytokine secretion was quantified by ELISA. An LPG1 null mutant was used to assess the contribution of virulence factor lipophosphoglycan (LPG) to the observed effects. Known protein virulence factors and LPG are present in L. mexicana EV fractions as well as known flagellar proteins. We show that there is a link between L. mexicana flagellar shortening and EV release, which is a recently discovered phenomenon in Chlamydomonas and mammalian cell research. We find that isolated EVs and live promastigotes induce changes in secreted cytokine levels from human and murine macrophages, including a substantial and previously unreported suppression of CXCL10, a chemokine which plays a protective role in Leishmania infection. LPG contributes to the effects observed on cytokine production, and EVs may be an important delivery mechanism for LPG.